Peripheral arterial disease in general and diabetic population - Rabia, K.; Khoo, Ee Ming (Malaysian Medical Association, 2007)
Peripheral arterial disease (PAD) is stenosis or occlusion of peripheral arterial vessels by atherosclerotic plaque. It may present as intermittent claudication, rest pain and impotence. PAD of the lower limbs is the third most important site of atherosclerotic disease after coronary heart disease and cerebrovascular disease. Increasing age, family history, smoking, hypertension, dyslipidemia and more decisively diabetes are significant risk factors. PAD is a clinical condition that has often been neglected, underdiagnosed, undertreated and has a serious outcome. It may lead to nonhealing wounds, gangrene and amputation of the lower limbs. Hence, early identification of patients at risk of PAD and timely referral to the vascular surgeon in severe cases is crucial.